A modified blatt dorsal capsulodesis in the treatment of dynamic scapholunate instability - Azura, L.Y.N.N.; Ahmad, Tunku Sara; Kamarul, Tunku (Malaysian Medical Association, 2006)
We report a case of scapholunate dissociation which was initially missed and presented late. A modification of Blatt dorsal capsulodesis performed using dorsal intercarpal ligament (DICL) and extra tunnel appears not only to add to dorsal stability but also address the volar problem as well. This modification may be a better alternative to the current technique of using a single flap.